Preferential orientations of structure directing agents in zeolites1. Issue 38 (14th October 2015) - Dib, Eddy; Gimenez, Antoine; Mineva, Tzonka; Alonso, Bruno
<x xml:space="preserve">Abstract</x> The local structure of MFI-type zeolites is modified using asymmetric tetraalkylammonium structure directing agents R(Pr)3N+ cations that adopt preferential orientations at the crossing between channels.